2021
DOI: 10.1016/j.jpainsymman.2020.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Medical Power of Attorney Completion for Hospitalized Patients During the COVID Pandemic: A Social Work Led Quality Improvement Intervention

Abstract: Background The high risk of mechanical ventilation with COVID hospitalizations requires health-care systems to rapidly innovate advance care planning (ACP) delivery for hospitalized patients to promote goal-concordant care. Measures Assess the impact of a social work and care management intervention on the proportion of admitted patients each week with a Medical Durable Power of Attorney (MDPOA). Intervention Social workers were consulted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…In some jurisdictions, only medical staff may initiate ACP conversations, with limited/no input from other multidisciplinary team members (Raftery et al, 2020; Singh et al, 2021). A large cohort study conducted in the US, found engaging social workers in ACP resulted in a 13% increase in patients nominating a medical POA (Singh et al, 2021). .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In some jurisdictions, only medical staff may initiate ACP conversations, with limited/no input from other multidisciplinary team members (Raftery et al, 2020; Singh et al, 2021). A large cohort study conducted in the US, found engaging social workers in ACP resulted in a 13% increase in patients nominating a medical POA (Singh et al, 2021). .…”
Section: Resultsmentioning
confidence: 99%
“…In some jurisdictions, only medical staff may initiate ACP conversations, with limited/no input from other multidisciplinary team members (Raftery et al, 2020;Singh et al, 2021). A large cohort study conducted in the US, found engaging social workers in ACP resulted in a 13% increase in patients nominating a medical POA (Singh et al, 2021).. A Taiwanese study noted local legal obligations to have two witnesses and associated costs might impede ACP (Lin et al, 2021). A narrative review during the pandemic (Gilissen et al, 2020) identified seven documents that described core ACP issues to be discussed with nursing home residents: POA (Enduring Guardian equivalent ), cardiopulmonary resuscitation (CPR), admission to hospital, intubation, non-invasive ventilation, fluids, antibiotics, etc.…”
Section: Barriers To Acp During Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 20 articles were included, of which eight were primary studies incorporating 5542 participants. The design of the primary studies was retrospective observational ( n = 4), 17–20 comparative cross‐sectional ( n = 1), 21 design process ( n = 2), 22,23 quality improvement intervention ( n = 1), 24 case report/study ( n = 2) 25,26 and virtual workshop ( n = 1) 27 . The rest of the articles were perspective papers ( n = 5), 3,28–31 letters to the editor ( n = 2), 32,33 newspaper analysis ( n = 1) 34 and guideline review ( n = 1) 35 .…”
Section: Resultsmentioning
confidence: 99%
“…SKMHT is a deed of agreement that is classified as a power of attorney in the form of lastgeving (volmacht), where SKMHT is a special letter that is only allowed by law to contain certain legal acts that are related to the imposition of dependent rights and is an irrevocable power and will not expire for any reason, therefore, SKMHT can be classified as an absolute power of attorney for material guarantees. If SKMHT has absolute power of attorney relating to material guarantees what about the regulations relating to the period of SKMHT if reviewed from the rules of the power of attorney in the Civil Code (Singh et al, 2021MacKay, 1992.…”
Section: Introductionmentioning
confidence: 99%